Monophyly and phylogenetic origin of the gall crab family Cryptochiridae (Decapoda: Brachyura) - Van Der Meij, S; Schubart, C (CSIRO Publishing, 2014)
The enigmatic gall crab family Cryptochiridae has been proposed to be phylogenetically derived from within the Grapsidae (subsection Thoracotremata), based on the analysis of 16S mtDNA of one cryptochirid, Hapalocarcinus marsupialis, among a wide array of thoracotremes, including 12 species of the family Grapsidae. Here, we test the monophyly and phylogenetic position of Cryptochiridae using the same gene, but with an extended representation of cryptochirids spanning nine species in eight of 21 genera, in addition to further thoracotreme representatives. The results show that gall crabs form a highly supported monophyletic clade within the Thoracotremata, which evolved independently of grapsid crabs. Therefore, the Cryptochiridae should not be considered as highly modified Grapsidae, but as an independent lineage of Thoracotremata, deserving its current family rank. Further molecular and morphological studies are needed to elucidate the precise placement of the cryptochirids within the Eubrachyura.